On the D5-brane description of 1 4 $$ \frac{1}{4} $$ -BPS Wilson loops in N $$ \mathcal{N} $$ = 4 super Yang-Mills theory - Alberto Faraggi; Cristóbal Moreno (Journal of High Energy Physics, 2024)
Abstract We construct the probe D5-brane solution in AdS 5 × S 5 dual to the 1 4 $$ \frac{1}{4} $$ -BPS latitude Wilson loop in N $$ \mathcal{N} $$ = 4 super Yang-Mills theory in the k-antisymmetric representation of SU(N). The solution is exact in the latitude parameter θ 0 and correctly reproduces the 1 2 $$ \frac{1}{2} $$ -BPS limit. We compute the string charge k and the renormalized on-shell action perturbatively to order O θ 0 10 $$ \mathcal{O}\left(θ_0^{10}\right) $$ and find full agreement with the expectation value of the Wilson loop predicted by the Gaussian matrix model in the limit N ∼ k → ∞, λ → ∞.